Author Index (Mazandaran University of Medical Sciences, 2015)
Aspergillus spp. are ubiquitous saprophytic fungi that cause a variety of diseases, ranging from hypersensitivity reactions to flulike pneumonia and life-threatening invasive aspergillosis. As the lung is the primary site of initial infection with airborne conidia, we investigated the innate immune responses of bronchial epithelial cells against different forms of Aspergillus spp.